Membangun Pendidikan yang Berkualitas: Antara Idealitas dan Realitas - Nabilah Khonsa; Rahmat Rizky Basuki; Lena Rusmiyati; Unifah Rosyidi; Muh. Takdir (Journal on Education, 2025)
Education plays a crucial role in forming quality human resources. However, several regions in Indonesia actually experience educational gaps. This study was conducted with the aim of determining the factors that cause educational gaps in Indonesia, the role of educational management in influencing the quality of education implementation in various regions, and solutions that can be applied to minimize gaps in the Indonesian education system using the Systemic Literature Review (SLR) method. The results of the study indicate that the factors causing gaps in the quality of education in Indonesia include limited education funds, limited resources and infrastructure, less than optimal teacher quality, and a non-data-based evaluation system. The role of educational management in influencing the quality of education in various regions includes several supporting components, such as Human Resources (HR) management, facilities and infrastructure management, financial management, and educational supervision. The solution to minimize gaps in the Indonesian education system can be done by maximizing education funds, improving the quality of facilities and infrastructure, organizing effective teacher professional development programs, and increasing the participation of all education stakeholders. The results of this study are important in order to reveal the gap between ideals and reality in Indonesian education.